Analisis Penerbitan Sukuk di Indonesia - kustiawan Abdurrahman, Kustiawan; Ihsan Arraafi, Muhamad; Ismail Azis, Widodo Dwi (UIN Sunan Gunung Djati Bandung, 2024)
Sukuk are long-term securities in which the corporate governance activities of the issuing company and the basis of the agreement refer to sharia principles which are then issued by the issuer to parties who have rights to the sukuk. Sukuk is an investment instrument that provides opportunities for Muslim investors and non-Muslim investors, both investors from Indonesia and abroad, to invest in Indonesia. The development of sukuk in Indonesia is expected to become a potential alternative source of state funding. This research is a literature study by reviewing and analyzing previous literature. The results of the analysis in the mechanism of issuance of sukuk require a number of certain assets which are the object of the agreement (underlying assets). These assets must have economic value, can be in the form of tangible or intangible assets, including projects that are in the delivery process. The function of these assets as a condition to avoid.